The Ius Constituendum Implementation of Simple Patents for the Management of Traditional Medicines - Juliana, Juliana; Kurniawan, I Gede Agus (Faculty of Law, Universitas Pekalongan, 2024)
Traditional medicine in Indonesia actually has the potential to be developed and has economic value for society. One effort to develop it is by optimizing aspects of intellectual property, especially through simple patents. This research aims to answer two legal issues, namely: the urgency of a simple patent orientation for traditional medicines in Indonesia and the formulation of a simple patent orientation for traditional medicines in Indonesia. This research method uses normative legal research with a conceptual and statutory approach. The research results confirm that the urgency of a simple patent orientation for the management of traditional medicines in Indonesia has three benefits at once, namely from the aspect of technology development, developing types of traditional medicine products, to increasing economic value. In the aspect of technology development, a simple patent for traditional medicine entrepreneurs can increase the value of creativity and innovation to always develop existing technology. Future arrangements that can be made are by establishing special regulations that regulate increasing the economic value of traditional medicines through the development of simple patents. Ideally, this regulation must also regulate three main substances, namely: an inventory of the potential for traditional medicines in a place, the potential for technological development through simple patents, and an effective and efficient marketing network for traditional medicines.